Осциляції нейтрино та антинейтрино. Експеримент NOvA - Nosek, T. (Publishing house "Academperiodika", 2019)
NOvA is a two-detector long-baseline neutrino oscillation experiment using Fermilab’s 700 kW NuMI muon neutrino beam. With a total exposure of 8.85×1020 +12.33×1020 protons on target delivered to NuMI in the neutrino + antineutrino beam mode (78% more antineutrino data than in 2018), the experiment has made a 4.4q-significant observation of the ve appearance in a vм beam, measured oscillation parameters |Δm232|, sin2O23, and excluded most values near бCP = п/2 for the inverted neutrino mass hierarchy by more than 3q.